Implementasi Nilai-nilai Kewarganegaraan dalam Pembentukan Karakter Siswa Madrasah Ibtidaiyah di Era Digital - Purnomo, Dian; Sari, Aisyah Elvina; Mufidah, Nabila Muna; Zulhidah (Journal of Practice Learning and Educational Development, 2026)
The development of digital technology has brought significant changes to the behavior, interaction patterns, and learning culture of Madrasah Ibtidaiyah (MI) students. This condition requires the strengthening of civic values to shape character based on morality, responsibility, and digital literacy. This study aims to describe the implementation of civic values in the character building process of MI students in Indragiri Hulu (INHU) Regency, Riau, with a focus on learning practices, madrasah culture, and the role of teachers and the digital environment. This study uses a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation of teachers, students, and madrasah principals. The results show that teachers apply civic values through the integration of civic education material, character building, role modeling, and the management of digital activities based on ethics and responsibility. Character building is also strengthened through digital literacy programs, supervision of gadget use, and social-based extracurricular activities. However, challenges arise in the form of low control over social media use at home and a lack of digital training for teachers. In conclusion, the implementation of civic values at MI INHU has been going well, although it still needs to be strengthened in terms of collaboration between schools and parents and improving teachers' digital competencies.